Increasing Patient Knowledge Through Education on Pulmonary Tuberculosis Treatment at the Galang Health Center, Tolitoli Regency: Peningkatan Pengetahuan Pasien Melalui Edukasi Pengobatan Tuberculosis Paru di Puskesmas Galang Kabupaten Tolitoli - Mutmainnah HS; Musdalipa Musdalipa (Salando Health Journal, 2024)
Tuberculosis is an infectious disease that can cause serious complications if not treated properly. Patients' knowledge of the treatment of pulmonary tuberculosis is still low, which often leads to non-adherence to treatment. This study aims to evaluate the effectiveness of pulmonary tuberculosis treatment education in increasing patient knowledge. The research used a quasi-experimental design with a one-group pretest-posttest method. Education was provided to 23 TB patients in the working area of the Galang Health Center, Tolitoli Regency. Education was provided for 3 consecutive days with interactive lecture methods and discussions using audiovisual media. The assessment was carried out before and after the education using a questionnaire sheet containing 10 question items about tuberculosis treatment that had been tested for validity and reliability. Data analysis using the wilcoxon test. The results showed that the respondents' knowledge before the intervention was 43.5% and after education increased to 95.7 in the good category and there was a significant increase in the patient's knowledge after being given education (p value = 0.001). This study recommends the implementation of ongoing education programs to support the success of TB treatment. The results of this study also provide long-term implications, namely helping to improve patient treatment compliance, prevent drug resistance, and reduce the burden of tuberculosis disease in the community.